Kajian Keamanan Bandara Sultan Mahmud Badaruddin II-Palembang - Rosidin Syamsudin (Research and Development Agency of The Ministry of Transportation, 2011)
An airport security from unlawful recruitment must start from the(acceptance) airport security personnel with the support of airport security equipment, as well as its security systems and procedures. Supervision of an airport security needs to be done since the area is not a public area where everyone is free to exit and enter without having to show identity card (Airport PAS), as well as passenger ticket. Furthermore, more stringent security controls imposed on the land side area airports (land side) up into the air side.